Influence of accessory sulci of the frontoparietal operculum on gray matter quantification - Vallejo-Azar, Mariana N.; Alba-Ferrara, Lucia; Bouzigues, Arabella; Princich, Juan P.; Markov, Martin; Bendersky, Mariana; Gonzalez, Paula N. (Frontiers in Neuroanatomy, 2023)
Introduction: The perisylvian region is the cortical core of language and speech. Several accessory sulci have been described in this region, whose presence could potentially modify the results of the automatic quantification of gray matter by popularly used software. This study aimed to assess the expression of accessory sulci in the frontoparietal operculum (FPO) and to evaluate their influence on the gray matter volume estimated by an automatic parcellation of cortical gyri and sulci. Materials and Methods: Brain MRI scans of 100 healthy adult volunteers were visually analyzed. The existence of the triangular and diagonal sulci, and the number of accessory sulci in the FPO, were assessed on T1 images. Also, the gray matter volume of gyri and sulci was quantified by an automatized parcellation method. Interhemispheric differences in accessory sulci were evaluated with Chi-square and Wilcoxon paired tests. The effect of the hemisphere, sex, age, total intracranial volume, and accessory sulci on morphometric variables was assessed by linear models. Results: Accessory sulci were found in more than half of the subjects, mostly in the left hemisphere and showed a significant effect on the gray matter content of structures of the FPO. In particular, the volume of the inferior frontal sulcus, pars opercularis of the inferior frontal gyrus, horizontal ramus of the lateral sulcus, angular gyrus, and postcentral gyrus parcellated and automatically quantified by Freesurfer showed a significant influence of the presence of accessory sulci. Conclusion: The prevalence of accessory sulci in the FPO is high, although their meaning is not yet known. This anatomical variability influences the quantification of gray matter. Therefore, they should be considered to reduce the risk of misclassifications of normal variation.